Mind7+: Mindfulness-based program for emotional regulation and focus, for university students – report December 2022 - Pinto, Paula (2022)
Mind7+ is a 8-week mindfulness-based structured program developed and applied to students of IPSantarém, with the aim of improving subjective well-being, emotional regulation, anxiety, depression, sleep quality, focus and healthy lifestyles. The program consisted 30H divided in 6 presential sessions and 2 online sessions, between 19th October and 14th December, 2022.